Analisis Yuridis terhadap Pelanggaran Izin Mendirikan Bangunan pada Kasus Hibisc Fantasy Puncak - Sevila Azka Monica (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze violations of Building Permits (IMB) committed by the manager of the Hibisc Fantasy Puncak tourist attraction in Bogor Regency. The approach used is normative legal research with analytical descriptive methods, supported by a literature study of relevant laws and regulations and legal literature. The results of the study indicate that construction was carried out on an area of ​​15,000 m², while permits were only granted for 4,800 m². This violation has a direct impact on environmental damage, especially flash floods, as well as causing social conflict and decreasing public trust in the government. Actions taken by the local government include demolition of illegal buildings and land rehabilitation, but weaknesses are still found in aspects of supervision and law enforcement. This study recommends the need for increased assertiveness in enforcing regulations, educating the public, and strengthening coordination between institutions to prevent future licensing violations.